Time Allocation Of Rubber Farmers In Cattle Farming As A Side Business: A Case Study Of The Ruminant Development Program In Batumarta II, OKU Regency - ahmad surahman; Endang Lastinawati; ema pusvita (Universitas Galuh, 2026)
This study aimed to analyze the allocation of working time among rubber farmers who also engaged in cattle farming as a side business under the Ruminant Development Program in Dusun Mekar Jati, Batumarta II, Ogan Komering Ulu (OKU) Regency, South Sumatra Province. The study was motivated by the phenomenon of livelihood diversification among rural farmers in Indonesia, where labor and time constraints were the main challenges in improving farming efficiency. OKU Regency was one of the central rubber plantation areas in South Sumatra that also actively participated in agricultural-livestock integration programs. Data were collected through observations and in-depth interviews with 14 farmers managing both types of businesses. Data were analyzed using a descriptive quantitative approach with non-parametric methods and average calculations of the Male Workday Equivalent (HKSP). The results showed that the average HKSP for rubber farming was 6.14, while cattle farming accounted for 4.28. This difference indicated that farmers allocated more time to rubber farming due to the nature of the work, which required routine and punctual activities such as tapping. On the other hand, cattle farming activities were more flexible and less time-consuming, often carried out outside of the main working hours. This study provided a new contribution to measuring time allocation for farmers engaged in dual enterprises simultaneously and filled a gap in the literature regarding labor efficiency in integrated farming systems. The study recommended the development of integrated farming models based on time efficiency and labor management to help farmers increase productivity and sustainable income. Keywords: HKSP, Farmers, Livelihood Diversification, Time Allocation